Al-Ghazali's Philosophical Thoughts on Combining Philosophy with Religious Teachings - Asep Zaenal Muttaqin; Fatma Husna Haibah Nurullah; Neng Zulfa Alawiyyah; Muhammad Wildan Nurfadillah (Penerbit Hellow Pustaka, 2025)
The philosophical thought of Al-Ghazali (1058–1111 CE) had a great influence on the Islamic intellectual tradition, especially in the relationship between reason and revelation. Al-Ghazali is known for his efforts to criticize and reduce the dominance of peripatetic philosophy influenced by Aristotelian thought, especially through his monumental work Tahafut al-Falasifah (The Confusion of the Philosophers). In this work, Al-Ghazali challenged the rationalistic view that considers reason as the only source of truth, stating that human reason has limitations that cannot reach absolute truth without divine revelation. In addition, Al-Ghazali criticized the views of philosophers such as Ibn Sina, who he said were unable to balance between rational philosophy and the spiritual dimension in the search for knowledge. His thinking also involved the importance of Sufism (Islamic mysticism), which was considered a more appropriate path to achieving a deeper understanding of God and the nature of human existence. Al-Ghazali argued that direct spiritual experience through contemplation and purification of the soul is far more profound than knowledge obtained only through reason and rational argument. In Ihya' 'Ulum al-Din, Al-Ghazali presents a practical ethics and philosophy that teaches self-control, simplicity, and a higher purpose in life as a means to attain closeness to God. By emphasizing the balance between reason, revelation, and spiritual experience, Al-Ghazali successfully combined philosophy with religious teachings, making a major contribution to the development of Islamic theological and philosophical thought that remains relevant today.